Lesotho Climate-Smart Agriculture Investment Plan : Opportunities for Transitioning to More Productive, Climate-Resilient, and Low Carbon Agriculture - World Bank (World Bank, Washington, DC, 2019)
Lesotho's agricultural system faces a growing number of climate-related vulnerabilities with droughts, floods, pests, and extreme temperatures occurring more frequently. In response, the Government of Lesotho is collaborating with the World Bank to integrate climate change into the country’s agriculture policy agenda through the Lesotho Climate-Smart Agriculture Investment Plan (CSAIP).